Robotik Kalp Cerrahisi Uygulamalarında Hemşirenin Sorumlulukları. - YAVUZ KARAMANOĞLU, Ayla; DEMİR KORKMAZ, Fatma (Turkiye Klinikleri Journal of Nursing Sciences, 2013)
Robotic surgery is defined as the surgical intervention conducted by the surgeon through a robot. Nurses should become sufficient in this field by completing theorical as practical educations as robotic surgical interventions require usage of complex medical devices. Utilization of robotic system in the operations changes the working environment of the nurses and also influences patient care. Therefore nurses should be ready for these technologic operations and fulfil patient care best. Nurses play a role in preparation and control of the system, placing and positioning the patient and providing the safety of the operative team in preoperative period of heart surgery. Nurses should primarily learn the equipment and the terminology of robotic surgery followed by learning to attach and detach and use the connections. They should also know making manoeuvres with robotic arms and clothing the arms and the camera with sterile coverings. In conclusion, it is certain that specialized nurses in robotic surgery field which is proposed to form the future of heart surgery are needed. In this paper, definitions of robotic surgery, the fields of usage robot in cardiac surgery, patient selection in robotic cardiac surgery, instruments using in robotic surgical operating room, features of robotic surgical operating room, education processes of specialised nurse in robotic cardiac surgery and preoperative, intraoperative and postoperative care of patients undergone robotic cardiac operation are given. It is thought that this article will make a contribution to those colleagues working in the units performing and planning for conducting robotic cardiac surgery.